Surface modification of two-dimensional layered double hydroxide nanoparticles with biopolymers for biomedical applications - Pavlovic, Marko; Szerlauth, Adél; Muráth, Szabolcs; Varga, Gábor; Szilagyi, Istvan (Advanced drug delivery reviews, 2022)
Layered double hydroxides (LDHs) are appealing nanomaterials for (bio)medical applications and their potential is threefold. One can gain advantage of the structure of LDH frame (i.e., layered morphology), anion exchanging property towards drugs with acidic character and tendency for facile surface modification with biopolymers. This review focuses on the third aspect, as it is necessary to evaluate the advantages of polymer adsorption on LDH surfaces. Beside the short discussion on fundamental and structural features of LDHs, LDH-biopolymer interactions will be classified in terms of the effect on the colloidal stability of the dispersions. Thereafter, an overview on the biocompatibility and biomedical applications of LDH-biopolymer composite materials will be given. Finally, the advances made in the field will be summarized and future research directions will be suggested.
Keywords: Nanoparticles; hydroxidy; nanočástice; Hydroxides; Biopolymers; Biopolymer; Carrier material; Nanocomposite; Surface modification; Adsorption; lidé; biopolymery; Layered double hydroxide; Humans; adsorpce